PENGARUH PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT DAN PENGUNGKAPAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN - Devi, Sunitha; Budiasih, I Gusti Nyoman; Badera, I Dewa Nyoman (UI Scholars Hub, 2017)
This research aims to find out empirical evidences on the effect of ERM disclosure and IC disclosure on firm value. The sample of the research is 73 non-financial companies listed in Indonesia Stock Exchange for the period of 2010-2014. Regression analysis of panel data was applied to analyze the data. The results show that ERM disclosure has positive and significant effect on the firm value. This study also finds that IC disclosure has positive and significant effect on the firm value. Firm size, profitability, and leverage, as control variables, are also contributing positive and significant effects on the firm value. The results of this research can be used as a consideration for the company’s management to increase ERM and IC disclosures in the annual report as ERM and IC disclosures can be a positive signal to encourage the increase in corporate value. In addition, since ERM and IC information are very significant for investors, it can also be beneficial for the regulator to set up and establish instruments of mandatory disclosure related to ERM and IC to minimize the asymmetry of information which can disadvantage company’s related parties.